Human immunodeficiency virus type 1 gp41 antibodies that mask membrane proximal region epitopes: antibody binding kinetics, induction, and potential for regulation in acute infection - Alam, S Munir; Scearce, Richard M; Parks, Robert J; Plonk, Kelly; Plonk, Steven G; Sutherland, Laura L; Gorny, Miroslaw K; Zolla-Pazner, Susan; Vanleeuwen, Stacie; Moody, M Anthony; Xia, Shi-Mao; Montefiori, David C; et al. (Journal of virology, 2008)
Two human monoclonal antibodies (MAbs) (2F5 and 4E10) against the human immunodeficiency virus type 1 (HIV-1) envelope g41 cluster II membrane proximal external region (MPER) broadly neutralize HIV-1 primary isolates. However, these antibody specificities are rare, are not induced by Env immunization or HIV-1 infection, and are polyspecific and also react with lipids such as cardiolipin or phosphatidylserine. To probe MPER anti-gp41 antibodies that are produced in HIV-1 infection, we have made two novel murine MAbs, 5A9 and 13H11, against HIV-1 gp41 envelope that partially cross-blocked 2F5 MAb binding to Env but did not neutralize HIV-1 primary isolates or bind host lipids. Competitive inhibition assays using labeled 13H11 MAb and HIV-1-positive patient plasma samples demonstrated that cluster II 13H11-blocking plasma antibodies were made in 83% of chronically HIV-1 infected patients and were acquired between 5 to 10 weeks after acute HIV-1 infection. Both the mouse 13H11 MAb and the three prototypic cluster II human MAbs (98-6, 126-6, and 167-D) blocked 2F5 binding to gp41 epitopes to variable degrees; the combination of 98-6 and 13H11 completely blocked 2F5 binding. These data provide support for the hypothesis that in some patients, B cells make nonneutralizing cluster II antibodies that may mask or otherwise down-modulate B-cell responses to immunogenic regions of gp41 that could be recognized by B cells capable of producing antibodies like 2F5.